อิทธิพลของอายุการตัดและรูปแบบปุ๋ยที่มีต่อผลผลิตชีวมวลและองค์ประกอบทางเคมีของหญ้าเนเปียร์ทิฟตันเพื่อใช้เป็นพลังงานทดแทน - ช่างประดิษฐ์ จุฑามาศ; โชติชุติมา ทรงยศ; สโรบล เอ็จ; ตัณมุขยกุล นพ (Thai Journal of Science and Technology, 2017)
บทคัดย่อ ศึกษาอิทธิพลของอายุการตัดและรูปแบบปุ๋ยที่มีต่อผลผลิตชีวมวลและองค์ประกอบทางเคมีของหญ้า เนเปียร์ทิฟตันเพื่อใช้เป็นพลังงานทดแทน แผนการทดลองแบบ Split-plot in RCBD จำนวน 4 ซ้ำ ประกอบด้วยปัจจัยหลัก คือ อายุการตัดที่ 120 วัน (A1), 150 วัน (A2) และ 180 วัน (A3) ปัจจัยรอง คือ การให้ปุ๋ย 4 รูปแบบ ได้แก่ ปุ๋ยยูเรีย อัตรา 36.8 กิโลกรัมไนโตรเจน/ไร่/ปี (T1), ปุ๋ยยูเรียผสมปุ๋ยคอกและใบกระถิน (ปุ๋ยยูเรีย อัตรา 18.4 กิโลกรัมไนโตรเจน/ไร่/ปี และปุ๋ยคอกผสมใบกระถิน (30 : 70, %w/w) อัตรา 18.4 กิโลกรัมไนโตรเจน/ไร่/ปี) (T2), ปุ๋ยคอกผสมใบกระถิน (30 : 70, %w/w) อัตรา 36.8 กิโลกรัมไนโตรเจน/ไร่/ปี (T3) และไม่ให้ปุ๋ยไนโตรเจน (T4) ผลการทดลองพบว่าผลผลิตน้ำหนักสดและแห้งภายใต้รูปแบบปุ๋ยทั้ง 4 นั้น ทรีทเมนต์ที่ได้รับปุ๋ยไนโตรเจน ได้แก่ ปุ๋ยยูเรีย (T1), ปุ๋ยยูเรียผสมปุ๋ยคอกผสมใบกระถิน (T2) และปุ๋ยอินทรีย์; ปุ๋ยคอกผสมใบกระถิน (T3) มีค่าสูงกว่า (P<0.05) ไม่ให้ปุ๋ยไนโตรเจน (T4) ปริมาณองค์ประกอบไฮโดรเจนของการตัดหญ้าเนเปียร์ที่อายุ 180 วัน (A3) ร่วมกับการได้รับปุ๋ยไนโตรเจนแบบ T1, T2 และ T3 มีค่าสูงกว่า (P<0.05) ทรีทเมนต์ที่เหลือ การตัดหญ้าเนเปียร์ที่อายุ 180 วัน (A3) ร่วมกับการใส่ปุ๋ยอินทรีย์ (T3) มีปริมาณองค์ประกอบไนโตรเจนและซัลเฟอร์สูงที่สุด (P<0.01) หญ้าเนเปียร์ที่อายุ 180 วัน (A3) ร่วมกับไม่ให้ปุ๋ยไนโตรเจน (T4) มีการสะสมคลอไรด์สูงที่สุด (P<0.01) และหญ้าเนเปียร์ที่อายุ 180 วัน (A3) ร่วมกับปุ๋ยอินทรีย์; ปุ๋ยคอกผสมใบกระถิน (T3) มีค่าพลังงานความร้อนสูงที่สุด (P<0.01) ซึ่งมีความเหมาะสมกับการนำไปใช้เป็นเชื้อเพลิงชีวมวลมากที่สุด คำสำคัญ : อายุการตัด; รูปแบบปุ๋ย; ผลผลิตชีวมวล; หญ้าเนเปียร์; ค่าพลังงานความร้อน Abstract The objective of this experiment was to study the influences of cutting ages and fertilizer forms on biomass yield and chemical compositions on Tifton napier grass for renewable energy. By experiment, Split-plot in RCBD with four replications consists of 2 factors. Major factor was cutting ages, at 120 days (A1), 150 days (A2) and 180 days (A3). Minor factor included 4 fertilizer forms, i.e. urea fertilizer rate 36.8 kg.N/rai/year (T1), urea fertilizer mixed with cow manure andleucaena leaf (urea fertilizer rate 18.4 kg.N/rai/year and a mix of cow manure and leucaena leaf (30:70, %w/w) rate 18.4 kg.N/rai/year) (T2), cow manure mixed with leucaena leaf (30 : 70, %w/w) rate 36.8 kg.N/rai/year (T3) and non-nitrogen fertilizer (T4). The results of fresh and dry weight yield under four fertilizer forms showed that grasses under three nitrogen fertilizer treatments urea fertilizer, T1, T2 and T3, produced higher fresh and dry weight than those of T4 (P<0.05). In part of hydrogen content, cutting grass at 180 days combination with the nitrogen fertilizer treatments including T1, T2 and T3 had higher (P<0.05) hydrogen content than the rest treatments. For nitrogen and sulfur content, cutting grass at 180 days (A3) combination with cow manure mixed leucaena leaf (T3) achieved the highest nitrogen and sulfur percentages (P<0.01). Moreover, chloride content of grass with cutting grass at 180 days (A3) combination with non-nitrogen fertilizer (T4) gave the highest chloride percentage (P<0.01). Furthermore, napier grass under cutting age 180 days (A3) combination with cow manure mixed leucaena leaf (T3) gave the highest value of heating value (P<0.01) which is suitable for using as biomass fuel. (T3) gave the highest (P<0.01) value of heating value which is suitable for using as biomass fuel. Keywords: cutting ages; fertilizer forms; biomass yield; napier grass; heating value